Breaking Through the Recruitment Barrier: Key Challenges and Proven Strategies for Hiring Managers (Global Journal of Management and Business Research, 2023)
ABSTRACT In today s competitive job market having the right strategy is crucial for hiring and onboarding top talent A recent survey conducted with 200 participants revealed that there are several important pillars of the hiring process including compelling outreach messaging the use of scheduling tools training and upskilling opportunities employee growth employer branding and clear communication By focusing on these pillars recruiters can achieve better and more efficient results during the recruitment process This paper aims to address the challenges faced by job seekers and leverages the insights of corporate professionals recruiters and hiring managers across diverse industries to identify six strategies that can simplify the hiring process for recruiters
Keywords: hiring; recruitment; job search; talent; human resource; on boarding; talent sourcing; jobs; recruiter; hiring manager